The jigsaw puzzle of fraudulent health claims: Missing psychological pieces. (August 2020) - Lilienfeld, Scott O.; Basterfield, Candice
Abstract: Fraudulent health claims have become an inescapable fixture of the contemporary information (or misinformation) landscape. MacFarlane, Hurlstone, and Ecker (2020) provided a five-fold framework for conceptualizing susceptibility to fraudulent health claims, and proposed potential remedies for each driver of these claims. We build on their analysis by arguing that a complete account of fraudulent health claim susceptibility additionally requires a thoroughgoing consideration of (a) individual differences in cognitive styles and personality traits, (b) innumeracy and statistical illiteracy, and (c) persuasive appeals involving logical fallacies and commonplaces. We further contend that dual processing models of cognition may help to synthesize a variety of psychological variables relevant to fraudulent health claim vulnerability. In conjunction with our commentary, MacFarlane's framework underscores the broader point that complex, multifactorial psychological phenomena demand complex, multifactorial psychological explanations and solutions.